Corrosion resistance and electrical conductivity of a nano ATO-doped MAO/methyltrimethoxysilane composite coating on magnesium alloy AZ31. (15th May 2020) - Li, Chang-Yang; Fan, Xiao-Li; Cui, Lan-Yue; Zeng, Rong-Chang
Highlights: An ATO-doped MAO/MTMS conductive coating is fabricated on Mg alloy AZ31. ATO-doped the MTMS surface layer acts as a conductive path. ATO-free of the middle MTMS coating acts as a physical barrier. Formation and corrosion resistance mechanisms of composite coatings are proposed. Abstract: An electrically conductive coating was prepared on micro-arc oxidized (MAO) Mg alloy AZ31 via antimony tin oxide (ATO) particles doping in methyltrimethoxysilane (MTMS) coating. A sandwich structure was observed as the ATO particles agglomerated at the top and bottom layers in the MTMS coating via field-emission scanning electron microscopy (FE-SEM). Electrochemical and hydrogen evolution tests revealed high corrosion resistance of the composite coating. Although the ATO-doped MAO/MTMS coating showed a low electrical conductivity, a conductive path was formed on the coating surface layer, enhancing the transfer of static charges. The formation and corrosion mechanisms of the composite coatings are proposed.